2005
DOI: 10.1016/j.amjhyper.2005.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Baroreflex Effectiveness Index in Hypertensive Patients With Chronic Renal Failure

Abstract: We conclude that BEI, which is markedly reduced in hypertensive patients with CRF, may convey information on arterial baroreflex function that is complementary to BRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 20 publications
1
31
2
1
Order By: Relevance
“…38 A more recent addition is the baroreflex effectiveness index, which estimates the number of times the baroreflex is active in controlling the heart rate in response to blood pressure fluctuations. 39 One recent study reported that reduced baroreflex effectiveness index and baroreceptor sensitivity are independent predictors of allcause mortality and SCD, respectively, in a cohort of patients with hypertension and chronic kidney disease. 40 …”
Section: Baroreceptor Sensitivity and Baroreflex Effectiveness Index mentioning
confidence: 99%
“…38 A more recent addition is the baroreflex effectiveness index, which estimates the number of times the baroreflex is active in controlling the heart rate in response to blood pressure fluctuations. 39 One recent study reported that reduced baroreflex effectiveness index and baroreceptor sensitivity are independent predictors of allcause mortality and SCD, respectively, in a cohort of patients with hypertension and chronic kidney disease. 40 …”
Section: Baroreceptor Sensitivity and Baroreflex Effectiveness Index mentioning
confidence: 99%
“…For example, there is evidence that asymmetric dimethylarginine (increased in renal failure, as a marker of endothelial dysfunction) may exert sympathoexcitatory effects, similar to what has been described for both angiotensin II and insulin (the circulating plasma levels of which are also increased in renal failure) [28]. Finally, there is evidence documenting that the reflex restraint exerted on adrenergic function by arterial baroreceptors is lost in patients with renal failure, suggesting the possibility that the adrenergic overdrive related to renal failure has a reflex nature [29].…”
Section: Sympathetic Activation and Renal Organ Damagementioning
confidence: 84%
“…Di Rienzo and coworkers [16] reported that sino-aortic denervation in cats reduced BEI to a value near zero supporting the contention that BEI was related to arterial baroreflex function. Even though the mechanisms behind a reduced BEI remain to be elucidated, a variable that is closely related to BEI, the number of baroreflex sequences have been reported to be reduced in patients with diabetes and a reduced BEI among chronic renal failure patients was related to diabetes suggesting that neuropathy of the autonomic peripheral nerves may influence BEI [19,20]. Neuropathy of the autonomic peripheral nerves seems less likely in the present population of middle-aged depressive patients without diabetes or overt cardiovascular diseases but central inhibitory influences affecting the cardiac vagal motor neurons of the prefrontal cortex and the insular cortex may prevail in major depressive disorder [21].…”
Section: Discussionmentioning
confidence: 98%